Keys to business communication success in college, career, and life - Carter, Carol (Pearson Education, 2012)
Clear and effective communication skills are necessary in every facet of student's-personal, academic, and professional. To help you become a well-rounded, successful communicator Keys to Business Communication provides the information you need so you can express yourself with confidence, clarity, and ease.